Uncertainty, Social Norms and Consumption Theory: Post and New Keynesian Approaches - Jan-Oliver Menz (Hamburg University, Department Economics and Politics, 2009)
Consumption theory has always been a neglected eld in Post Keynesian economics, whereas it is at the center of New Keynesian economics. This paper investigates similarities and differences between the two approaches. I will show that the newer mainstream models indeed give results that are fairly similar, even if differences, especially concerning methodological questions, still remain. Building on insights from Economic Sociology and Behavioral Economics, the importance for consumption theory of an adequate treatment of risk and uncertainty on the one hand and the role of social norms on the other hand is emphasized.
Keywords: E21; E12; D11; 330; Uncertainty; Social Norms; Consumption Theory; Post Keynesianism; New Keynesianism